2014
DOI: 10.5897/ajb2014.13915
|View full text |Cite
|
Sign up to set email alerts
|

Canonical correlations in elephant grass for energy purposes

Abstract: Elephant gr other chara multivariate The objectiv traits and b the groups energy. The dos Goytac and third e evaluated: percentage third cut, in percentage evaluated. T canonic co cuts isolate content and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The six most productive genotypes with best biomass quality were selected and evaluated according to the results obtained by Rossi et al (2014), as follows: Cubano Pinda, Mercker 86-México, Pusa Napier n°1, Mole de Volta Grande, P-241-Piracicaba, and King Grass.…”
Section: Methodsmentioning
confidence: 99%
“…The six most productive genotypes with best biomass quality were selected and evaluated according to the results obtained by Rossi et al (2014), as follows: Cubano Pinda, Mercker 86-México, Pusa Napier n°1, Mole de Volta Grande, P-241-Piracicaba, and King Grass.…”
Section: Methodsmentioning
confidence: 99%
“…Genotype yield demonstrates why elephant grass stands out among energy crops [35], and with total possibility of insertion into the Brazilian energy matrix consolidated by the use of sugarcane and eucalyptus, mainly by the amount of biomass produced and the production cycle [2]. [12], evaluating elephant grass cultivars in the Northeast region of Brazil, observed that BRS Canará and Cubano Pinda obtained ADMY ranging from 66.3 to 84.3 ton DM ha -1 year -1 at 6 months of cultivation.…”
Section: Stem Diameter Tillers Number Dry Matter Yield and Annual Dmentioning
confidence: 99%
“…A total of 15 hybrids from crosses between ten elephant grass genotypes were evaluated (Table 1), previously selected according to studies for biomass production, adding some traits, such as late flowering, dry matter yield, stem diameter, number of tillers [12].…”
Section: Elephant Grass Genotypes Testedmentioning
confidence: 99%